Leitura de Imagens na sala de aula : arte, cultura visual e intertextualidade - Silva, Alexandra Moura da (2017)
This article discusses advertisements reading within a dialog with Brazilian modern art through intertext, in order to enlarge pupil knowledge. It follows Santaella's method based on semiotics principles. As a result it shows an experience report of an intervention made by pupils from a Brazilian Public School. It concludes reflecting over the relevance of visual reading on learning